Human matters in asthma: Considering the microbiome in pulmonary health - Marathe, Sandesh J.; Snider, Mark A.; Flores-Torres, Armando S.; Dubin, Patricia J.; Samarasinghe, Amali E. (Frontiers in Pharmacology, 2022)
Microbial communities form an important symbiotic ecosystem within humans and have direct effects on health and well-being. Numerous exogenous factors including airborne triggers, diet, and drugs impact these established, but fragile communities across the human lifespan. Crosstalk between the mucosal microbiota and the immune system as well as the gut-lung axis have direct correlations to immune bias that may promote chronic diseases like asthma. Asthma initiation and pathogenesis are multifaceted and complex with input from genetic, epigenetic, and environmental components. In this review, we summarize and discuss the role of the airway microbiome in asthma, and how the environment, diet and therapeutics impact this low biomass community of microorganisms. We also focus this review on the pediatric and Black populations as high-risk groups requiring special attention emphasizing that the whole patient must be considered during treatment. Although new culture-independent techniques have been developed and are more accessible to researchers, the contribution the airway microbiome makes in the pathogenesis of asthma is not well understood. Understanding how the airway microbiome, as a living entity in the respiratory tract, participates in lung immunity during the development and progression of asthma may lead to critical new interventions for asthma, including population-targeted interventions, or even more effective administration of currently available therapeutics.